P-Coumaric acid quantum dots inhibit beta lactam resistant foodborne microorganisms. (2020) - Zulkarnain, Mohammad Zulhazim; Tong, Woei Yenn; Tan, Wen-Nee; Leong, Chean Ring; Md Yusof, Fahmi Asyadi; Wahidin, Suzana; Attifah, Nur Rifqah; Zubaidah, Siti
Abstract: Foodborne diarrhoeal diseases are linked to the deaths of over 1.8 million people annually. The antimicrobial activity of p-coumaric acid was reported, however the application was limited due to poor water solubility. Quantum dot technology can be applied to overcome these limitations. Thus, we aimed to synthesize and characterize p-coumaric acid quantum dot by wet milling technique. Besides, the antimicrobial efficiency of the quantum dots was also tested on foodborne pathogens. The spherical shaped quantum dots were successfully synthesized. The average size of the quantum dots was 8.9 ± 3.7 nm with a zeta potential of −3.73 mV. The synthesis of quantum dot also increased the water solubility of p-coumaric acid to 1.98%. On disc diffusion assay, p-coumaric acid quantum dot exhibited significant inhibitory on various beta-lactam resistant test bacteria. The quantum dots inhibited the growth of all Gram- positive test bacteria, 5 Gram negative bacteria and 1 yeast. The antimicrobial performance was significantly better compared to free p-coumaric acid. The activity of p-coumaric acid quantum dot was microbicidal with a wide range of minimal inhibitory concentrations (31.25–500.00 µg/ml). On time kill analysis, p-coumaric acid quantum dots displayed concentration dependent killing capacity on Staphylococcus aureus and Proteus mirabilis. At concentration of minimal lethality concentration, 99.9% killing of bacterial cells were observed throughout the experimental period. A significantly lower bacterial growth was observed relative to control. In conclusion, p-coumaric acid quantum dots were successfully synthesized. The quantum dots exhibited significant antimicrobial activity on wide spectrum of foodborne microorganisms. The study suggested that the application of p-coumaric acid quantum dots in food system may be effective in inhibiting the growth of foodborne microorganisms.